Method for producing zinc phenylphosphonate complex, powder of zinc phenylphosphonate complex, use of the same as a crystal nucleating agent, and moisture-curable hot-melt urethane resin adhesive

JP7639994B2Active Publication Date: 2025-03-05DIC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024536475
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-15
Publication Date
2025-03-05
Estimated Expiration
2042-09-15

AI Technical Summary

Benefits of technology

【0009】 本発明の一側面によれば、湿気硬化性ホットメルトウレタン樹脂の固化時間を更に短縮できる結晶核剤として好適に使用可能なフェニルホスホン酸亜鉛錯体の製造方法及びフェニルホスホン酸亜鉛錯体の粉末を提供することができる。また、本発明の他の一側面によれば、固化時間が更に短縮された湿気硬化性ホットメルトウレタン樹脂接着剤を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639994000001
    Figure 0007639994000001
  • Figure 0007639994000002
    Figure 0007639994000002
  • Figure 0007639994000003
    Figure 0007639994000003
Patent Text Reader

Abstract

The present invention aims to provide a method for producing a zinc phenylphosphonate complex that can be suitably used as a crystal nucleating agent capable of further shortening the solidification time of a moisture-curable hot-melt urethane resin, and a powder of the zinc phenylphosphonate complex. Another aspect of the present invention aims to provide a moisture-curable hot-melt urethane resin adhesive having a further shortened solidification time. [Solution] A method for producing a phenylphosphonic acid zinc complex, comprising the step of reacting phenylphosphonic acid represented by formula (1) with a zinc compound in water in the presence of polyethylene glycol. TIFF2024546373000009.tif2563
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a zinc phenylphosphonate complex, a powder of the zinc phenylphosphonate complex, its use as a crystal nucleating agent, and a moisture-curable hot-melt urethane resin adhesive. [Background technology]

[0002] Moisture-curing hot-melt urethane resins have excellent adhesive properties and the adhesive time can be adjusted relatively freely, making them suitable for use as adhesives in adhesive processing and molding processes such as sealing, which require continuous production, and are used in a wide range of fields. However, in applications such as wood wrapping for decorative sheets that require initial strength, and in electrical and electronic parts and automotive parts that require continuous production on high-speed lines, problems can arise in that the urethane resin moves to the next process without being sufficiently cooled and solidified.

[0003] In order to solve the above problems, the metal salt of phenylphosphonic acid compound is added to urethane resin as a crystal nucleating agent to shorten the solidification time.For example, WO 2011 / 030822 discloses a method for producing a phenylphosphonic acid metal salt suitable as a crystal nucleating agent, which is characterized by reacting a phenylphosphonic acid compound with a metal salt, metal oxide or metal hydroxide in an amount exceeding its equivalent. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2011 / 030822 Summary of the Invention [Problem to be solved by the invention]

[0005] According to the investigations of the present inventors, when a metal phenylphosphonate is used as a crystal nucleating agent, there is room for further shortening the solidification time of the moisture-curable hot-melt urethane resin.

[0006] Therefore, one aspect of the present invention aims to provide a method for producing a zinc phenylphosphonate complex that can be suitably used as a crystal nucleating agent that can further shorten the solidification time of a moisture-curable hot-melt urethane resin, and a powder of the zinc phenylphosphonate complex. Another aspect of the present invention aims to provide a moisture-curable hot-melt urethane resin adhesive with a further shortened solidification time. [Means for solving the problem]

[0007] The present inventors have found that by causing polyethylene glycol to coexist when reacting phenylphosphonic acid with a zinc compound in water, it is possible to obtain a phenylphosphonic acid zinc complex and a powder thereof that can be suitably used as a crystal nucleating agent that can further shorten the solidification time of a moisture-curable hot-melt urethane resin.

[0008] The present invention includes the following aspects. [1] A method for producing a phenylphosphonic acid zinc complex, comprising the step of reacting phenylphosphonic acid represented by formula (1) with a zinc compound in water in the presence of polyethylene glycol. TIFF0007639994000001.tif2563[2] The method according to [1], wherein the amount of the zinc compound is 1 mole or less per mole of the phenylphosphonic acid represented by formula (1). [3] A powder of a phenylphosphonic acid zinc complex represented by formula (2), obtained by the production method according to [1] or [2]. TIFF0007639994000002.tif2563[4] Use of the powder described in [3] as a crystal nucleating agent. [5] A moisture-curable hot-melt urethane resin adhesive comprising an isocyanate-terminated urethane prepolymer and the powder described in [3]. [6] The moisture-curable hot-melt urethane resin adhesive according to [5], wherein the powder content is 0.1 to 10 mass % based on the total amount of the moisture-curable hot-melt urethane resin adhesive. Effect of the Invention

[0009] According to one aspect of the present invention, there is provided a method for producing a zinc phenylphosphonate complex that can be suitably used as a crystal nucleating agent capable of further shortening the solidification time of a moisture-curable hot-melt urethane resin, and a powder of the zinc phenylphosphonate complex. According to another aspect of the present invention, there is provided a moisture-curable hot-melt urethane resin adhesive having a further shortened solidification time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention will be described in detail. One embodiment of the present invention is a method for producing a phenylphosphonic acid zinc complex, comprising a step (reaction step) of reacting phenylphosphonic acid represented by formula (1) with a zinc compound in water in the presence of polyethylene glycol. TIFF0007639994000003.tif2563

[0011] In the reaction step, for example, an aqueous solution of phenylphosphonic acid represented by formula (1) dissolved in water is added with an aqueous solution of a zinc compound dissolved in water and a solution of polyethylene glycol dissolved in a solvent to react the phenylphosphonic acid represented by formula (1) with the zinc compound. At this time, the above reaction can be progressed by gradually adding an aqueous alkali solution such as an aqueous sodium hydroxide solution.

[0012] The amount of water in the aqueous solution of phenylphosphonic acid represented by formula (1) may be 1,000 parts by mass or more, 2,000 parts by mass or more, or 3,000 parts by mass or more, and may be 10,000 parts by mass or less, 7,000 parts by mass or less, or 5,000 parts by mass or less, relative to 100 parts by mass of phenylphosphonic acid represented by formula (1).

[0013] The zinc compound may be, for example, a zinc halide, zinc oxide, or zinc acetate. The zinc halide may be zinc fluoride, zinc chloride, zinc bromide, or zinc iodide.

[0014] The amount of water in the aqueous solution of the zinc compound may be 500 parts by mass or more, 1000 parts by mass or more, or 2000 parts by mass or more, and may be 5000 parts by mass or less, 4000 parts by mass or less, or 3000 parts by mass or less, relative to 100 parts by mass of the zinc compound.

[0015] The amount of the zinc compound may be 0.8 mol or more, 0.9 mol or more, or 0.95 mol or more, and may be 1.1 mol or less, 1.05 mol or less, or 1 mol or less, relative to 1 mol of the amount of the phenylphosphonic acid represented by formula (1).

[0016] The number average molecular weight (Mn) of the polyethylene glycol may be 200 or more, 500 or more, or 800 or more, and may be 2000 or less, 1500 or less, or 1200 or less.

[0017] The solvent for dissolving the polyethylene glycol may be an alcohol. The alcohol may be an aliphatic alcohol. Examples of the alcohol include methanol, ethanol, 1-propanol, 2-propanol, and ethylene glycol.

[0018] The amount of the solvent in the polyethylene glycol solution may be 100 parts by mass or more, 150 parts by mass or more, or 200 parts by mass or more, and may be 400 parts by mass or less, 350 parts by mass or less, or 300 parts by mass or less, relative to 100 parts by mass of polyethylene glycol.

[0019] The white precipitate formed by the above reaction step is filtered, washed with water, and then dried to obtain the phenylphosphonic acid zinc complex represented by formula (2) as a powder (white powder). That is, another embodiment of the present invention is a powder of the phenylphosphonic acid zinc complex represented by formula (2) obtained by the above production method. TIFF0007639994000004.tif2563

[0020] The powder of the phenylphosphonic acid zinc complex represented by formula (2) is obtained by the above-mentioned manufacturing method, and therefore can further shorten the solidification time of the moisture-curable hot melt urethane resin, as compared with, for example, a commercially available powder of the phenylphosphonic acid zinc complex. Although it is unclear what structure or characteristic of the powder of the phenylphosphonic acid zinc complex represented by formula (2) is responsible for such an effect, the present inventors speculate that the reason for the above-mentioned effect is as follows. Since polyethylene glycol can function as a dispersion medium in the reaction process, the dispersibility of the crystals in water is improved during crystallization of the phenylphosphonic acid zinc complex represented by formula (2), and crystals (powder) with little aggregation can be obtained. When this powder is mixed with a urethane resin as a crystal nucleating agent, the contact area between the crystal nucleating agent and the urethane resin increases, which is thought to promote the crystallization of the urethane resin.

[0021] In one embodiment, the powder of the zinc phenylphosphonate complex represented by formula (2) is obtained by the above-mentioned production method, and therefore, compared to, for example, commercially available powders of zinc phenylphosphonate complex, it is possible to achieve a shortened tack-free time of the moisture-curable hot-melt urethane resin adhesive, improved initial creep properties, and improved initial peel strength.

[0022] As described above, the powder of the phenylphosphonic acid zinc complex represented by formula (2) can be suitably used as a crystal nucleating agent, more specifically, as a crystal nucleating agent that promotes the crystallization of a urethane resin. That is, another embodiment of the present invention is the use (application) of the powder of the phenylphosphonic acid zinc complex represented by formula (2) as a crystal nucleating agent (a crystal nucleating agent that promotes the crystallization of a urethane resin).

[0023] Another embodiment of the present invention is a moisture-curable hot-melt urethane resin adhesive containing an isocyanate-terminated urethane prepolymer and a powder of a zinc phenylphosphonate complex represented by the above formula (2).

[0024] The isocyanate group-terminated urethane prepolymer can be obtained by reacting a polyol (A) with a polyisocyanate (B) in the presence of a zinc phenylphosphonate complex represented by the above formula (2) and a zinc phosphate complex represented by the above formula (4).

[0025] The polyol (A) may contain an aliphatic polyester polyol, may contain two types of aliphatic polyester polyols (the aliphatic polyester polyol (a1) and the aromatic polyester polyol (a2) described below), or may contain two types of aliphatic polyester polyols (the aliphatic polyester polyol (a1) and the aromatic polyester polyol (a2) described below) and a polyol (a3) ​​other than the aliphatic polyester polyol.

[0026] The aliphatic polyester polyol (a1) is a polyester polyol produced from an aliphatic polycarboxylic acid and an aliphatic polyol as main components by a known and commonly used method, and the production method is not particularly limited.

[0027] The aliphatic polycarboxylic acid used in the synthesis of the aliphatic polyester polyol (a1) is preferably an aliphatic polycarboxylic acid having 4 to 12 carbon atoms, such as succinic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decanedioic acid, dodecanedioic acid, eicosadionic acid, citraconic acid, itaconic acid, citraconic anhydride, or itaconic anhydride.

[0028] The aliphatic polycarboxylic acids may be used in the form of corresponding acid derivatives, such as lower alkyl ester derivatives (eg, methyl esters), acid anhydrides, acid halides, etc.

[0029] The aliphatic polyol used in the synthesis of the aliphatic polyester polyol (a1) has at least two hydroxyl groups in the molecule, and is preferably an aliphatic polyol having a carbon number of 2 to 12. The (a1) may have any of a linear, branched, or cyclic structure.

[0030] Examples of the aliphatic polyol include linear aliphatic polyols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, diethylene glycol, triethylene glycol, and tetraethylene glycol, and neopentyl glycol, 1,3-butanediol, and 2,2-diethyl-1,3-propanediol. , 2,2-diethylpropanediol, 3-methyl-1,5-pentanediol, 2-ethyl-2-butyl-1,3-propanediol, 2-methyl-1,8-octanediol, 2,4-diethyl-1,5-pentanediol, trimethylolethane, trimethylolpropane, pentaerythritol, and other branched aliphatic polyols; and cyclopentanediol, cyclohexanediol, cyclohexanedimethanol, and other alicyclic polyols. Of these, ethylene glycol, 1,6-hexanediol, and neopentyl glycol are preferred.

[0031] Also usable are adducts in which various alkylene oxides are added to hydrogenated bisphenol A, hydrogenated bisphenol F, etc. Also usable are polymers in which γ-butyrolactone, ε-caprolactone, etc. are subjected to ring-opening polymerization using a low molecular weight polyol as an initiator. These may be used alone or in combination of two or more.

[0032] Among the combinations of the aliphatic polycarboxylic acids and the aliphatic polyols, it is preferable to incorporate an aliphatic polyester polyol (a1) produced by combining an aliphatic polycarboxylic acid having 4 to 12 carbon atoms with an aliphatic polyol having 2 to 12 carbon atoms in the polyol (A), since this further improves the viscosity stability during molding of the hot-melt urethane resin adhesive and provides an excellent effect in preventing a decrease in the melt viscosity.

[0033] The aromatic polyester polyol (a2) is a polyester polyol produced by a known, commonly used method using an aromatic polycarboxylic acid and an aliphatic polyol, or an aliphatic polycarboxylic acid and an aromatic polyol, as the main components, and the production method is not particularly limited.

[0034] The aromatic polycarboxylic acid is a carboxylic acid having at least two carboxyl groups bonded to an aromatic ring, and is preferably an aromatic polycarboxylic acid having 8 to 24 carbon atoms, and examples thereof include orthophthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, pyromellitic acid, biphenyldicarboxylic acid, naphthalenedicarboxylic acid, etc. These may be used alone or in combination of two or more kinds.

[0035] The aromatic polycarboxylic acids may be used in the form of corresponding acid derivatives, such as lower alkyl ester derivatives (eg, methyl esters), acid anhydrides, acid halides, etc.

[0036] Examples of the aliphatic polyol include the same aliphatic polyols as those usable in the synthesis of the aliphatic polyester polyol (a1).

[0037] The aliphatic polyol usable in the synthesis of the aromatic polyester polyol (a2) and the aliphatic polyester polyol (a1) may be, for example, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,4-bis(β-hydroxyethoxy)benzene, etc., in which a portion of the carbon atoms is substituted with an oxygen atom or an aromatic ring. These aliphatic polyols may be used alone or in combination of two or more kinds.

[0038] Furthermore, it may be a mixture of polyester polyols obtained from these aromatic polycarboxylic acids and aliphatic polyols.

[0039] Examples of the aliphatic polycarboxylic acid that can be used in the synthesis of the aromatic polyester polyol (a2) include aliphatic polycarboxylic acids having 4 to 12 carbon atoms similar to the aliphatic polycarboxylic acids that can be used in the synthesis of the aliphatic polyester polyol (a1).

[0040] The aromatic polyol is not particularly limited, but examples thereof include aliphatic polyols such as ethylene glycol and neopentyl glycol, and aromatic polyols obtained from aromatic polycarboxylic acids such as orthophthalic acid and terephthalic acid.

[0041] Furthermore, as the aromatic polyol, for example, an adduct of bisphenol A, bisphenol F, or the like with an alkylene oxide such as ethylene oxide, propylene oxide, or butylene oxide can also be used.

[0042] The equivalent ratio (i.e., [OH / COOH equivalent ratio]) of the hydroxyl groups of the aliphatic polyol and aromatic polyol to the carboxyl groups of the aliphatic polycarboxylic acid and aromatic polycarboxylic acid during synthesis of the aliphatic polyester polyol (a1) and aromatic polyester polyol (a2) is preferably in the range of 1.03 to 1.50, and more preferably in the range of 1.05 to 1.30. When the [OH / COOH equivalent ratio] is in this range, a larger amount of hydroxyl-terminated polyol can be produced, and the urethane reaction with the polyisocyanate (B) can proceed more easily, which is preferable.

[0043] The polycondensation conditions for the synthesis of the aliphatic polyester polyol (a1) and the aromatic polyester polyol (a2) are not particularly limited as long as they do not cause abnormal reactions and can produce normal products. Usually, a given amount of aliphatic polycarboxylic acid and aliphatic polyol, or aromatic polycarboxylic acid and aliphatic polyol, are subjected to an esterification reaction or an ester exchange reaction at an internal temperature of 150 to 250°C for 5 to 50 hours in the presence or absence of a catalyst, and then a polycondensation reaction is carried out.

[0044] The polycondensation reaction is preferably carried out in the presence of a catalyst, since the reaction proceeds easily. The catalyst is not particularly limited, and examples thereof include titanium-based catalysts such as titanium tetrabutoxide and tin-based catalysts such as dibutyltin oxide.

[0045] The catalyst may be charged together with the aliphatic polyol and the aliphatic polycarboxylic acid, or together with the aliphatic polyol and the aromatic polycarboxylic acid, or may be added after prepolymerization without a catalyst.

[0046] In the production of the aliphatic polyester polyol (a1) and aromatic polyester polyol (a2), it is desirable to convert most of the terminals to hydroxyl groups and to leave as few carboxyl terminal groups as possible. For this purpose, it is effective and preferable to add the catalyst after carrying out preliminary polymerization.

[0047] The number average molecular weight (hereinafter referred to as "Mn") of the aliphatic polyester polyol (a1) and the aromatic polyester polyol (a2) is preferably in the range of 500 to 6000, more preferably in the range of 1000 to 5000, and particularly preferably in the range of 2000 to 4000. If the Mn of the (a1) and (a2) is in this range, a balance of physical properties such as strength and elongation depending on the application can be obtained, which is preferable.

[0048] Examples of the other polyols (a3) ​​include polycarbonate polyols, polylactone polyols, polyether polyols, etc. Examples of the polycarbonate polyols include polycarbonate polyols obtained by using the linear aliphatic polyols such as 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, etc. Examples of the polylactone polyols include polycaprolactone polyols obtained by ring-opening polymerization of caprolactone monomers, etc. Examples of the polyether polyols include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc.

[0049] The content ratio of the aliphatic polyester polyol (a1) / the aromatic polyester polyol (a2) / the other polyol (a3) ​​may be 20-60 parts by mass / 10-50 parts by mass / 0-50 parts by mass, preferably 30-50 parts by mass / 20-40 parts by mass / 10-20 parts by mass, in 100 parts by mass of the polyol (A). If the content ratio is within this range, the melt viscosity of the polyol (A) can be adjusted to an appropriate range, and a moisture-curable hot melt urethane resin adhesive having excellent workability and compatibility and further excellent solidification properties can be obtained.

[0050] The polyisocyanate (B) may be a known and commonly used aliphatic, aromatic, or alicyclic polyisocyanate, such as diphenylmethane diisocyanate (MDI; its 4,4', 2,4', or 2,2' form, or a mixture thereof, crude MDI), carbodiimide-modified MDI (modified MDI), polymethylene polyphenyl polyisocyanate, carbodiimidized diphenylmethane polyisocyanate, xylene diisocyanate, tolylene diisocyanate (TDI; its 2,4 form, or 2,6 form, or a mixture thereof), xylylene diisocyanate (XDI), 1,5-naphthalene diisocyanate (NDI), tetramethylxylene diisocyanate, phenylene ... Examples of the diisocyanates include aromatic diisocyanates such as hexamethylene diisocyanate (HDI), dimer acid diisocyanate, norbornene diisocyanate, lysine diisocyanate, tetramethyl xylylene diisocyanate, and other aliphatic diisocyanates; and alicyclic diisocyanates such as isophorone diisocyanate (IPDI), hydrogenated diphenylmethane diisocyanate (hydrogenated MDI), hydrogenated xylylene diisocyanate (hydrogenated XDI), cyclohexane diisocyanate, dicyclohexylmethane diisocyanate, and isophorone diisocyanate. Among these, MDI and XDI are preferred because they react quickly with the polyol (A) and moisture (water) and have excellent workability. These may be used alone or in combination of two or more.

[0051] The ratio of the polyol (A) and the polyisocyanate (B) used in synthesizing the isocyanate group-terminated urethane prepolymer (hereinafter referred to as "prepolymer") may be within a range that does not adversely affect reaction behavior or product quality, and is usually preferably in the range of 1.2 to 4.0, more preferably 1.5 to 3.0, as the equivalent ratio (hereinafter referred to as [NCO / OH equivalent ratio]) between the isocyanate group of the polyisocyanate (B) and the hydroxyl group of the polyol (A). If the [NCO / OH equivalent ratio] is within this range, the melt viscosity of the intended moisture-curable hot melt urethane resin composition will be in an appropriate range, and excellent workability, film properties, and further excellent solidification properties can be expressed.

[0052] The reaction conditions are not particularly limited as long as they are set within a range that does not adversely affect the reaction behavior or product quality, but it is usually preferable to carry out the reaction at a reaction temperature of 80 to 130° C. for 1 to 10 hours.

[0053] The reaction system may be selected from known reaction systems such as a batch reaction, a semi-continuous reaction, or a continuous reaction.

[0054] The reaction can be carried out in a solvent or without a solvent. However, when the reaction is carried out in a solvent, it is preferable to remove the solvent during or after the reaction, and finally to make the reaction solvent-free. The method of removing the solvent is not particularly limited.

[0055] The content of the powder of the phenylphosphonic acid zinc complex represented by formula (2) may be 0.1 mass% or more, 10 mass% or less, or 0.1 to 10 mass% based on the total amount of the moisture-curable hot-melt urethane resin adhesive. The lower limit of the total amount may be 0.3 mass%, 0.5 mass%, or 1 mass% based on the total amount of the moisture-curable hot-melt urethane resin adhesive. The upper limit of the total amount may be 7 mass%, 5 mass%, or 3 mass% based on the total amount of the moisture-curable hot-melt urethane resin adhesive.

[0056] The moisture-curable hot-melt urethane resin adhesive of the present embodiment may further contain other resins such as conventionally known thermoplastic resins and thermosetting resins, and may further contain other additives. Examples of other additives include foam stabilizers, antioxidants, defoamers, UV absorbers, abrasive grains, fillers, pigments, dyes, colorants, thickeners, surfactants, flame retardants, plasticizers, lubricants, antistatic agents, heat stabilizers, tackifiers, curing catalysts, stabilizers, fluorescent brighteners, silane coupling agents, waxes, etc.

[0057] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0058] [Example 1] (Production of Phenylphosphonic Acid Zinc Complex) In a 1-liter 4-neck flask, 10 parts by mass of phenylphosphonic acid represented by formula (1) (63.3 mmol) and 400 parts by mass of water were added to prepare an aqueous solution. An aqueous solution prepared from 8.6 parts by mass (63.1 mmol) of zinc chloride and 200 parts by mass of water, and 6.9 parts by mass of polyethylene glycol (Mn=1000) dissolved in 19.7 parts by mass of ethanol were further added to this flask and mixed. With stirring, 129 parts by mass of 1.0 M aqueous sodium hydroxide solution was added to this aqueous solution over 3 hours to cause a reaction. The precipitated white precipitate was filtered, washed with water, and then dried under reduced pressure at 80°C for 2 hours or more to obtain a phenylphosphonic acid zinc complex represented by formula (2) as a white powder.

[0059] (Manufacture of moisture-curing hot melt urethane resin adhesives) In a 1-liter four-neck flask, 30 parts by mass of polypropylene glycol (Mn=1000), 40 parts by mass of aliphatic polyester polyol (Mn=4500) obtained by reacting 1,6-hexanediol (HD) and adipic acid (AA) in a HD / AA=46 / 54 mass ratio, and 30 parts by mass of aromatic polyester polyol (Mn=5000) obtained by reacting 1,6-hexanediol (HD), neopentyl glycol (NPG), ethylene glycol (EG), isophthalic acid (iPA), and terephthalic acid (tPA) in a HD / NPG / EG / iPA / tPA=7 / 14 / 18 / 40 / 21 mass ratio were mixed and melted to prepare polyol (A). Next, 1.2 parts by mass (1.0% by mass based on the total amount of the adhesive) of the powder of the phenylphosphonic acid zinc complex represented by formula (2) obtained above was added to the above (A) as a crystal nucleating agent, and the mixture was heated to 110°C and dehydrated under reduced pressure conditions until the moisture content became 0.05% by mass. Thereafter, the mixture was cooled to 70° C., 19 parts by mass of 4,4-diphenylmethane diisocyanate was added, and the mixture was reacted at 90° C. for 3 hours until the NCO content (%) became constant, to obtain a moisture-curable hot-melt urethane resin adhesive.

[0060] [Comparative Example 1] The same procedure as in Example 1 was carried out, except that the powder of the zinc phenylphosphonate complex represented by formula (2) obtained above was not added, to obtain a moisture-curable hot-melt urethane resin adhesive.

[0061] [Comparative Example 2] The same procedure was carried out as in Example 1, except that a commercially available powder of phenylphosphonic acid zinc complex, Ecopromote (manufactured by Nissan Chemical Industries, Ltd.), was used instead of the powder of phenylphosphonic acid zinc complex represented by formula (2) obtained above, to obtain a moisture-curable hot-melt urethane resin adhesive.

[0062] [Comparative Example 3] In Example 1, the same procedure was carried out except that a commercially available powder of phenylphosphonic acid zinc complex, Ecopromote-NP (manufactured by Nissan Chemical Industries, Ltd.), was used instead of the powder of phenylphosphonic acid zinc complex represented by formula (2) obtained above, to obtain a moisture-curable hot-melt urethane resin adhesive.

[0063] [Evaluation of solidification time (open time)] The obtained moisture-curable hot-melt urethane resin adhesive of each of the examples and comparative examples was heated to a molten state at 120°C and applied to a polypropylene sheet substrate to a thickness of 50 μm. Next, kraft paper was placed as a surface member on the adhesive layer applied above, and immediately left in a thermostatic chamber at 35°C. The time (unit: second) until the kraft paper no longer adhered to the adhesive layer was measured from the time point when it was left in the thermostatic chamber, and this was taken as the solidification time at 35°C (open time at 35°C). Furthermore, the time (unit: second) until the adhesive layer was touched and lost its adhesive feel was measured from the time point when it was left in the thermostatic chamber, and this was taken as the tack-free time at 35°C. The results are shown in Table 1.

[0064] [Evaluation of initial creep properties] The obtained moisture-curing hot-melt urethane resin adhesive was heated to a molten state at 120°C, and the molten moisture-curing hot-melt urethane resin adhesive was applied to a 1-inch-wide polypropylene sheet to a thickness of 50 μm, and then MDF (medium density fiberboard) was placed on the applied adhesive layer and bonded. Three minutes after bonding, a load of 150 g was applied to the MDF in a 90° direction in an atmosphere of 35°C, and the time (seconds) until the peel length reached 4 cm was measured, which was taken as the initial creep property at 35°C. The results are shown in Table 1.

[0065] [Evaluation of initial peeling strength] The obtained moisture-curing hot-melt urethane resin adhesive was heated to a molten state at 120°C, and the molten moisture-curing hot-melt urethane resin adhesive was applied to a 1-inch-wide polypropylene sheet to a thickness of 50 μm, and then MDF (medium density fiberboard) was placed on the applied adhesive layer and bonded. Three minutes after bonding, the MDF was peeled in a 180° direction in a room temperature atmosphere, and the tensile strength (N) at that time was measured and used as the initial peeling strength after 3 minutes. The results are shown in Table 1.

[0066] [Table 1] TIFF0007639994000005.tif47155

Claims

1. A method for producing a phenylphosphonic acid zinc complex, comprising the step of reacting phenylphosphonic acid represented by formula (1) with a zinc compound in water in the presence of polyethylene glycol.

2. The method according to claim 1, wherein the amount of the zinc compound is 1 mole or less per mole of the phenylphosphonic acid represented by the formula (1).

Citation Information

Patent Citations

  • Flame-retardant aromatic polycarbonate resin composition and molding of the same

    JP2013237799A

  • Method for producing phosphonic acid metal salt fine particles

    WO2010131678A1

  • Method for producing phosphonic acid metal salt and thermoplastic resin composition containing phosphonic acid metal salt

    WO2011030822A1